2016
DOI: 10.3389/fonc.2016.00166
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cells Abolish Melanoma Tumorigenesis in Hemoglobin SS Knockin Mice and Augment the Tumoricidal Effect of Oncolytic Virus In Vivo

Abstract: Insights from the study of cancer resistance in animals have led to the discovery of novel anticancer pathways and opened new venues for cancer prevention and treatment. Sickle cells (SSRBCs) from subjects with homozygous sickle cell anemia (SCA) have been shown to target hypoxic tumor niches, induce diffuse vaso-occlusion, and potentiate a tumoricidal response in a heme- and oxidant-dependent manner. These findings spawned the hypothesis that SSRBCs and the vasculopathic microenvironment of subjects with SCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The SSRBC-mediated vessel occlusions were often clustered and tightly packed with erythrocytes of which nearly 100% exhibited a sickle cell morphology ( Figure 7C). Because only 5% of circulating nondeformable sickle cells in SSKI mice display the sickle morphology (15), it is likely that SSRBCs trapped in the injured tumor microvessels transitioned to the sickle shape as their HbS deoxygenated and polymerized. That therapy with SR and CA-4 in SSKI but not AAKI mice can induce tumor regression in vivo confirms the key role of SSRBCs in the vaso-oc- Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSRBC-mediated vessel occlusions were often clustered and tightly packed with erythrocytes of which nearly 100% exhibited a sickle cell morphology ( Figure 7C). Because only 5% of circulating nondeformable sickle cells in SSKI mice display the sickle morphology (15), it is likely that SSRBCs trapped in the injured tumor microvessels transitioned to the sickle shape as their HbS deoxygenated and polymerized. That therapy with SR and CA-4 in SSKI but not AAKI mice can induce tumor regression in vivo confirms the key role of SSRBCs in the vaso-oc- Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Intravital microscopy observations show that infused SSRBCs home to established tumor, form aggregates in tumor vessels, and induce focal vessel closure. Together with pro-oxidants or oncogenic virus, SSRBCs also induce a therapeutic tumor growth delay but fail to produce complete tumor regressions (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we showed that cytotoxic drugs could be physically encapsulated in SSRBCs and programed ex vivo to discharge 4 times more drug cargo into hypoxic tumors relative to normal RBCs and free drug . Likewise, SSRBCs loaded with oncolytic reovirus directed the virus to melanoma in vivo and exhibited increased tumoricidal effectiveness relative to similarly treated normal RBCs and free virus . While osmosis‐based encapsulation allows the entrapment of large quantities of biologics it also injures cell membranes and alters the circulatory kinetics of the modified RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…9 Likewise, SSRBCs loaded with oncolytic reovirus directed the virus to melanoma in vivo and exhibited increased tumoricidal effectiveness relative to similarly treated normal RBCs and free virus. 10 While osmosisbased encapsulation allows the entrapment of large quantities of biologics it also injures cell membranes and alters the circulatory kinetics of the modified RBCs. Physical entrapment is confined to a limited group of agents and release at the targeted site can be unpredictable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation